2018
DOI: 10.1103/physrevlett.121.107201
|View full text |Cite
|
Sign up to set email alerts
|

Floquet Engineering of Multiorbital Mott Insulators: Applications to Orthorhombic Titanates

Abstract: We consider driving multiorbital Mott insulators using laser radiation. We derive general expressions for periodically driven spin-orbital models using time-dependent perturbation theory in the strong interaction limit. We show that the effective exchange interactions of the Floquet spin-orbital Hamiltonian are highly tunable via variations of the frequency, amplitude, and polarization of the laser. We also take the effect of a finite bandwidth of excitations into account and study possible heating effects. We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 72 publications
0
48
0
Order By: Relevance
“…Strong spin-orbit coupled multi-orbital compounds constitute a natural generalization of such a nonequilibrium separation of charge and spin degrees of freedom (Arakawa and Yonemitsu, 2021;Hejazi et al, 2019;Liu et al, 2018;Sriram and Claassen, 2021), which could allow for Floquet engineering while mitigating heating. In the orthorhombic titanates, the partially-filled t 2g manifold has been proposed as a prime target for optical manipulation of effective Kugel-Khomskii spin-orbital interactions.…”
Section: Engineering Correlated Systemsmentioning
confidence: 99%
“…Strong spin-orbit coupled multi-orbital compounds constitute a natural generalization of such a nonequilibrium separation of charge and spin degrees of freedom (Arakawa and Yonemitsu, 2021;Hejazi et al, 2019;Liu et al, 2018;Sriram and Claassen, 2021), which could allow for Floquet engineering while mitigating heating. In the orthorhombic titanates, the partially-filled t 2g manifold has been proposed as a prime target for optical manipulation of effective Kugel-Khomskii spin-orbital interactions.…”
Section: Engineering Correlated Systemsmentioning
confidence: 99%
“…The results in this limit can be interpreted as the behavior of the system when exposed to static external field, and thus is a reflection of the (static) field-induced breakdown of a Mott insulator. In a prior short paper [42], some parts of this formalism were presented, and applied to the orthorhombic titanates YTiO 3 and LaTiO 3 using first-principles calculations. It was observed that as a result of multi-orbital interactions, ferromagnetic and antiferromagnetic Mott insulators exhibit distinct responses to laser radiation.…”
mentioning
confidence: 99%
“…Floquet engineering with optical fields is a valuable technique that could induce topological band structures and electronic correlations in various materials [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Floquet engineering of TBG has been considered as a technique to tune the value of the magic angle using longitudinal waves [36], and to control the topology of the bands near the CNP at large twist angles [37].…”
Section: Introductionmentioning
confidence: 99%